2009
DOI: 10.1590/s0100-29452009000300037
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescência da clorofila a em folhas de tangerineira 'Ponkan' e limeira ácida 'Tahiti' submetidas ao estresse hídrico

Abstract: O trabalho foi realizado com o objetivo de avaliar o estresse causado por deficiência hídrica para induzir o florescimento sobre a fluorescência da clorofila a em tangerineira 'Ponkan' e limeira ácida 'Tahiti'. As plantas foram enxertadas sobre o limoeiro 'Cravo', conduzidas em câmara de crescimento sob condições controladas. O estresse causado pela deficiência hídrica submetido à tangerineira 'Ponkan' e à limeira ácida 'Tahiti' reduziu a eficiência quântica potencial do fotossistema II (Fv/Fm). Após a irrigaç… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 10 publications
(8 reference statements)
2
3
0
3
Order By: Relevance
“…Likewise, Dias & Marenco (2007) also attribute this increase in Fo to the damage in the D1 protein, inactivating PSII. Cruz et al (2009) conducted studies on the fluorescence of leaves of 'Ponkan' mandarin and 'Tahiti' acid lime subjected to water stress and concluded that Fo values increased proportionally to the water stress levels, corroborating the results obtained in the present study.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Likewise, Dias & Marenco (2007) also attribute this increase in Fo to the damage in the D1 protein, inactivating PSII. Cruz et al (2009) conducted studies on the fluorescence of leaves of 'Ponkan' mandarin and 'Tahiti' acid lime subjected to water stress and concluded that Fo values increased proportionally to the water stress levels, corroborating the results obtained in the present study.…”
Section: Resultssupporting
confidence: 89%
“…The obtained results allow inferring that, under the experimental conditions, the irrigation water with ECw above 1.8 dS m -1 caused damages to the photosynthetic apparatus of 'Mimo do Céu' orange, a fact evidenced by the reduction in the photochemical efficiency of PSII, 0.73. Cruz et al (2009) observed that the lowest value in the Fv/Fm ratio was 0.320 in citrus cultivars subjected to water stress, recovering with subsequent irrigation. Silveira et al (2010) report that plants subjected to salinity have low quantum yield, probably due to stomatal closure and decrease in photosynthesis, physiological mechanisms that may have occurred with the plants subjected to saline stress in this experiment.…”
Section: Resultsmentioning
confidence: 95%
“…Moreover, corroborating Araújo et al (2010), the authors also hypothesize that decreases in Fv Fm -1 ratios can actually reflect certain photochemical adjustments that plants may adopt under adverse weather and soil conditions, and is not a consequence of damage to PS2, noting that the decrease in the Fv Fm -1 ratio can result from an increase in the initial fluorescence (Fo). This finding is consistent with that of Cruz et al (2009), who reported that an increase in Fo causes increased loss of excitation energy during its transfer among antenna pigments and reaction centers, and thereby constitutes a factor that contributes significantly to a decrease in the Fv Fm -1 ratio. According to Gonçalves et al (2010), there is no consensus in the literature regarding what effects a decrease in soil water availability may produce on the Fv Fm -1 ratio.…”
Section: As the Water Supply Becomes Limiting Transpiration Decreasesupporting
confidence: 92%
“…A respeito de algumas características fisiológicas observáveis em plantas submetidas a estresse, vários autores (KONRAD et al, 2005;CRUZ et al, 2009;MELO et al, 2010;SUASSUNA et al, 2010) têm analisado a fluorescência da clorofila a no estudo de mecanismos fotossintéticos em plantas condicionadas a estresse bióticos e abióticos como temperatura, radiação solar, deficiência hídrica, salinidade, presença de patógenos e herbicidas. Nesse contexto, o uso de parâmetros de fluorescência tem sido difundido, principalmente, no estudo de fotossíntese por ser um método que, além de não-destrutivo, permite análise qualitativa e quantitativa da absorção e aproveitamento da energia luminosa por meio do fotossistema II e possíveis relações com a capacidade fotossintética (NETTO; CAMPOSTRINI; .…”
Section: )unclassified